2023
DOI: 10.1109/access.2022.3232983
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Fuzzy Supplementary Controller for SSR Damping in a Series-Compensated DFIG-Based Wind Farm

Abstract: Although using a series compensation technique in a long transmission line effectively increases the transmittable power; it may cause a sub-synchronous resonance (SSR) phenomenon. Gatecontrolled series capacitor (GCSC) is an effective method for SSR damping by controlling the turn-off angle. In the previous studies, a constant supplementary damping controller (SDC) was used for controlling the turnoff angle, which can mitigate the SSR phenomenon. However, these methods can not capture the maximum transmittabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The results showed that the threshold value for the current signal is higher than the threshold value for voltage signal because the sub-synchronous component within the current signal is more obvious than the sub-synchronous component within the voltage signal. The SSO was detected after 0.1 s. On the basis of the previous works, the researchers have used different input signals such as current signal [9,21,22], voltage signal [6,10,14,21], active power signal [11], and both the electrical and mechanical signals [7,12,18]. In [6], the SSO detection methods that have been published before 2020 have been summarized in terms of the used approach, input signal, and SSO detection time.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the threshold value for the current signal is higher than the threshold value for voltage signal because the sub-synchronous component within the current signal is more obvious than the sub-synchronous component within the voltage signal. The SSO was detected after 0.1 s. On the basis of the previous works, the researchers have used different input signals such as current signal [9,21,22], voltage signal [6,10,14,21], active power signal [11], and both the electrical and mechanical signals [7,12,18]. In [6], the SSO detection methods that have been published before 2020 have been summarized in terms of the used approach, input signal, and SSO detection time.…”
Section: Introductionmentioning
confidence: 99%
“…The results proved the effectiveness and capability of this method for SSR damping at high compensation levels and low wind speeds. In reference [14], a fuzzy logic controller was proposed to compute the gain of SDC based on the wind speed and the error between the measured and reference line currents for transferring as much power as possible and damping the SSR phenomenon simultaneously. Since the GCSC is so far from the wind farm location, the use of local signals is more reliable than remote ones to avoid communication issues, ensure continuous operation, and achieve a lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…Doubly-fed induction generator (DFIG) has been widely used in the field of wind power generation because of its small converter capacity and variable speed constant frequency power generation [1]. However, a large number of static Var compensators and series compensation capacitors are connected to the power grid in the process of UHV power transmission, resulting in sub-synchronous oscillation (SSO) and power quality decline [2], [3], [4]. Power grid SSO will affect the stability of wind power generation, which will lead to wind…”
Section: Introductionmentioning
confidence: 99%